Mobile phone use for empowerment in the context of social exclusion: an ethnographic study of urban refugees in South Africa - Bisimwa, Kasky Bacishoga (Department of Information Systems, 2018)
Problem Statement: Calls have been made to find ways to address the problem of urban refugees who are now acknowledged as a universal, continuing, and recurring phenomenon. There is a dominant optimism about the contribution of mobile phones to the empowerment of refugees in the host countries. However, there is a dearth of knowledge on exactly how mobile phones contribute to empowerment, and also the use of mobile phones by urban refugees in developing countries has received only minimal attention. The purpose of the research: The main objective of this research was to empirically investigate whether the use of mobile phones by urban refugees in South Africa generates or fails to generate capabilities for empowerment. The specific aim was to critically explore the factors which shape the use of mobile phones by urban refugees in South Africa and their capabilities for empowerment. Design / methodology / approach: This research adopted a critical orientation to knowledge, used critical ethnographic methods and drew on a theoretical lens developed from the integration of Sen's Capability Approach and Bourdieu's Theory of Practice. The data were collected through observations and in-depth interviews with 22 urban refugees in South Africa. Documents and website corroborating evidence have provided secondary data. Data were analysed using thematic analysis. Findings: The findings suggest that mobile phone use affords valuable capabilities for empowerment in three main ways. First, the capabilities to negotiate ways to participate in the information society by: participating in economic and financial activities, improving access to services and to sources of information. Second, the capabilities to effectively engage with wider networks by: developing and maintaining relationships, being socially and culturally connected, and communicating effectively. Third, the capabilities to manage one's own situation and solve problems by: multi-tasking easily, and a guarantee of transparency and security. However, the generation of these capabilities is contingent on power relations in the social field - between social structures and individual's agency. In South Africa, the capabilities of empowerment that urban refugees can generate through mobile phone use are either enhanced or hindered by interrelated factors, namely the affordances of mobile phones, socio-environmental factors, and personal factors. The availability of capital is very crucial for personal factors, to which they confer more, or less, power to influence the power relations. Originality / contribution: This research contributes to the theory in the field of Information Systems by proposing a dynamic framework with precise constructs for theorising and explaining the mechanisms and social practices that shape mobile phone use and the capabilities for empowerment. This research suggests that to research mobile phone use for empowerment in the context of social exclusion and inequality in developing countries, researchers need to look beyond social agents' immediate behaviours to take into consideration the broader context of social exclusion, by focusing on conversion factors, human diversity, and capabilities. This research has exposed the explicitly or implicitly hidden interests, important beliefs, assumptions and social practices that facilitate or constrain capabilities for empowerment. It contributes to the empowerment of the ethnographic researcher who is himself an urban refugee in South Africa, but also to the empowerment of urban refugees in South Africa and perhaps of other individuals in a similar situation. That is because empowerment starts with the enlightenment and the realisation of one's own true interest and situation. The findings can also contribute to the policy-setting process of government or organisations seeking to assist urban refugees, by facilitating the formulation of their intervention strategies.